2017
DOI: 10.1186/s40562-017-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Rebuild of the Bulletin of the International Seismological Centre (ISC), part 1: 1964–1979

Abstract: The data from the Bulletin of the International Seismological Centre (ISC) have always been and still remain in demand for a wide range of studies in Geosciences. The unique features of the Bulletin include long-term coverage (1904-present), the most comprehensive set of included seismic data from the majority of permanent seismic networks at any given time in the history of instrumental recording (currently ~ 150) and homogeneity of the data and their representation. In order to preserve this homogeneity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 21 publications
0
64
0
1
Order By: Relevance
“…The number of stations reporting amplitudes increased until World War II, dropped in the 1940s and improved significantly from 1953. European and many Russian stations are the most important contributors to amplitude readings compared to stations in other continents, except for La Paz (LPZ, Observatorio San Calixto, Bolivia) and Riverview College (RIV, Sydney, Australia) from the Jesuit seismic network (Udías and Stauder, 1996). The number of stations per event contributing amplitudes ranges from 0 to above 40, with the median per year oscillating from 0 to 6 ( Fig.…”
Section: Station Data Collection and Earthquake Selectionmentioning
confidence: 99%
“…The number of stations reporting amplitudes increased until World War II, dropped in the 1940s and improved significantly from 1953. European and many Russian stations are the most important contributors to amplitude readings compared to stations in other continents, except for La Paz (LPZ, Observatorio San Calixto, Bolivia) and Riverview College (RIV, Sydney, Australia) from the Jesuit seismic network (Udías and Stauder, 1996). The number of stations per event contributing amplitudes ranges from 0 to above 40, with the median per year oscillating from 0 to 6 ( Fig.…”
Section: Station Data Collection and Earthquake Selectionmentioning
confidence: 99%
“…Here we use a unique agency code for these source mechanisms and replace the HRVD agency code with the GCMT code throughout the ISC Bulletin. This is already done for the time period 1976-1979 covered by the first part of the ISC rebuild project (1964( -1979( , Storchak et al, 2017. After completion of the ISC rebuild project, all remaining HRVD source mechanism solutions will be available under the GCMT code.…”
Section: Source Mechanism Contributions To the Isc Bulletinmentioning
confidence: 99%
“…Since then new focal mechanisms have routinely been added for every data month added in the Reviewed ISC Bulletin. Moreover, we have published focal mechanism solutions obtained from reported polarities for the ISC-relocated earthquakes (m ISC b > 3.5) covering the time period 1964-1984 as part of the rebuild project (Storchak et al, 2017) and focal mechanism solutions obtained from reported polarities in the ISS Bulletins (see http://www.isc.ac.uk/ projects/focalmechs/, last access: April 2019). The gap currently shown in Fig.…”
Section: Source Mechanism Contributions To the Isc Bulletinmentioning
confidence: 99%
“…The data is sent to the user's e-mail as mini-seed, full-seed or dataless (SEED File). (Storchak et al, 2017). Figure 6.1 compares the ISC locations before and after the Rebuild project for the entirety of the released rebuilt ISC Bulletin from 1964 to 1990.…”
Section: Turkey Earthquake Data Center System (Tdvm)mentioning
confidence: 99%